Different flavours of oxygen help quantify seasonal variations of the biological carbon pump in the Celtic Sea - Seguro, Isabel; Marca, Alina D.; Shutler, Jamie D.; Kaiser, Jan (Frontiers in Marine Science, 2023)
Shelf seas represent only 10% of the World’s Ocean by area but support up to 30% of its primary production. There are few measurements of biological production at high spatial and temporal resolution in these physically and biologically dynamic systems. Here, we use dissolved oxygen to-argon (O2/Ar) ratios and oxygen triple isotopes in O2 (16O, 17O, 18O) to estimate net community production, N(O2/Ar), and gross O2 production, G(17O), in summer and autumn 2014 and spring and summer 2015 in the Celtic Sea, as part of the UK Shelf-Sea Biogeochemistry Programme. Surface O2/Ar concentration ratios were measured continuously using a shipboard membrane inlet mass spectrometer. Additional depth profiles of O2/Ar concentration ratios, δ(17O) and δ(18O) were measured in discrete water samples from hydrocasts. The data were combined with wind-speed based gas exchange parameterisations to calculate biological air-sea oxygen fluxes. These fluxes were corrected for diapycnal diffusion, entrainment, production below the mixed layer, and changes over time to derive N(O2/Ar) and G(17O). The Celtic Sea showed the highest G(17O) in summer 2014 (825 mmol m–2 d–1) and lowest during autumn 2014 (153 mmol m–2 d–1). N(O2/Ar) was highest in spring 2015 (43 mmol m–2 d–1), followed by summer 2014 (42 mmol m–2 d–1), with a minimum in autumn 2014 (–24 mmol m–2 d–1). Dividing the survey region into three hydrographically distinct areas (Celtic Deep, Central Celtic Sea and Shelf Edge), we found that Celtic Deep and Shelf Edge had higher N(O2/Ar) in summer (71 and 63 mmol m–2 d–1, respectively) than in spring (49 and 22 mmol m–2 d–1). This study shows regional differences in the metabolic balance within the same season, as well as higher net community production in summer than in spring in some areas and years. The seasonal patterns in biological production rates and the export efficiency (f-ratio) identified the importance of biology for supporting the Celtic Sea’s ability to act as a net CO2 sink. Our measurements thus help improve our understanding of the biological carbon pump in temperate shelf seas.